Dual antiplatelet therapy duration after coronary stenting in clinical practice: results of an EAPCI survey - Valgimigli, Marco; Costa, Francesco; Byrne, Robert; Haude, Michael; Baumbach, Andreas; Windecker, Stephan; Vavlukis, Marija; Boshev, Marijan (EuroPCR, 2015)
Our aim was to report on a survey initiated by the European Association of Percutaneous Cardiovascular Interventions (EAPCI) concerning opinion on the evidence relating to dual antiplatelet therapy (DAPT) duration after coronary stenting.
Aims: Our aim was to report on a survey initiated by the European Association of Percutaneous Cardiovascular Interventions (EAPCI) concerning opinion on the evidence relating to dual antiplatelet therapy (DAPT) duration after coronary stenting. Methods and results: Results from three randomised clinical trials were scheduled to be presented at the American Heart Association Scientific Sessions 2014 (AHA 2014). A web-based survey was distributed to all individuals registered in the EuroIntervention mailing list (n=15,200) both before and after AHA 2014. A total of 1,134 physicians responded to the first (i.e., before AHA 2014) and 542 to the second (i.e., after AHA 2014) survey. The majority of respondents interpreted trial results consistent with a substantial equipoise regarding the benefits and risks of an extended versus a standard DAPT strategy. Two respondents out of ten believed extended DAPT should be implemented in selected patients. After AHA 2014, 46.1% of participants expressed uncertainty about the available evidence on DAPT duration, and 40.0% the need for clinical guidance. Conclusions: This EAPCI survey highlights considerable uncertainty within the medical community with regard to the optimal duration of DAPT after coronary stenting in the light of recent reported trial results. Updated recommendations for practising physicians to guide treatment decisions in routine clinical practice should be provided by international societies. © Europa Digital & Publishing 2015. All rights reserved.
Keywords: Drug Administration Schedule; Drug Therapy; Combination; Evidence-Based Medicine; Surveys; Percutaneous Coronary Intervention; Platelet Aggregation Inhibitors; Treatment; Outcome